Perilaku Kepemimpinan Kepala Sekolah dalam Peningkatan Kinerja Guru - Juwita, Ratna; Rohayani, Ai (Perkumpulan Peneliti dan Pegiat Literasi, 2022)
The principal's leadership behavior should be able to influence the behavior of subordinates to want to work together productively, efficiently, and effectively in order to achieve organizational goals. The success of an organization, both as a whole and various group in a particular organization is very dependent on the quality of leadership contained in the organization concerned. One of the successes of the principal's leadership behavior is to improve teacher performance. A qualified teacher means that the teacher is also a good teacher. A good and qualified teacher has characteristics in the form of a number of competencies. These competencies are teacher effectiveness, teacher cognitive ability, teacher personality, classroom management, mastery of information technology, and commitment and responsibility. This paper aims to present a discussion of principals' leadership behavior in improving teacher performance. This research is a qualitative field research with the research location in SMP Muhammadiyah Sukaraja, Sukabumi Regency. The data in this study were obtained from the results of observations, interviews, and documentation studies. The results of this study reveal that the principal's policy in improving the ability of teachers at SMP Muhammadiyah Sukaraja, Sukabumi Regency has made written and oral rules according to the school's vision and mission by involving teachers, school targets and school principals to formulate activities to improve teacher abilities such as: KKG. In addition, the principal as a leader in improving the discipline of teachers at SMP Muhammadiyah Sukaraja, Sukabumi Regency makes programs using good communication. This is reinforced by the principal's strategy as a leader in increasing the responsibility of teachers at SMP Muhammadiyah Sukaraja, Sukabumi Regency by involving all teachers and providing direct examples.